Upaya Peningkatan Semangat Belajar Siswa Materi Lingkungan Hidup dengan Model PjBL Berbantuan Media Pembelajaran Inovatif pada Jurusan Teknik Otomotif - Janah, Alfitrotul (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Natural and Social Sciences (IPAS) is one of the subjects that is only given in class X in the independent curriculum for Vocational Senior High School (SMK) students. Based on the results of observations, the low enthusiasm for IPAS subjects is because IPAS is a complex subject that combines material from biology, physics, chemistry, and social science so that there is a lot of theory to understand, while vocational schools are expected to have a lot of practical learning so that it is boring for students. Project-based learning (PjBL) is assumed to be very suitable as an implementation solution and is also very dominant in vocational-based schools. The study aimed to determine the increase in enthusiasm for studying science and technology in class X majoring in automotive engineering at SMK Takhassus Wonosobo. The subjects in this classroom action research were 40 students majoring in automotive engineering in environmental matters. The data collection method is in the form of observation sheets and documentation. Based on the empirical data that has been obtained through this research, it shows that before the action the data on students' learning enthusiasm reached 47.50 with the Less Enthusiastic (MB) criteria. After the action was held in cycle I, it increased to the level of 53.75 which also met the criteria for Less Enthusiastic (KB) but these results had not yet reached an indicator of success so the researchers held a follow-up cycle where students' enthusiasm for learning reached 62.50 or with the criteria Enthusiastic (B). Therefore, PjBL learning assisted by innovative media has succeeded in increasing the enthusiasm for learning science and science in class X majoring in automotive engineering, SMK Takhassus Wonosobo